Financial accounting - Libby, Robert; Libby, Patricia A.; Short, Daniel G. (Chicago : Irwin, 1996)
Business
2000-07-19
Keywords: Financial accounting; Financial statement; Business decision; Transaction analysis; Accounting information; Sales revenue; Reporting; Cash flows